2005
DOI: 10.1111/j.1742-4658.2005.04625.x
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Phanerochaete chrysosporium Cel7D in complex with product and inhibitors

Abstract: The cellobiohydrolase Pc_Cel7D is the major cellulase produced by the white‐rot fungus Phanerochaete chrysosporium, constituting ≈10% of the total secreted protein in liquid culture on cellulose. The enzyme is classified into family 7 of the glycoside hydrolases and, like other family members, catalyses cellulose hydrolysis with net retention of the anomeric carbon configuration. Previous work described the apo structure of the enzyme. Here we investigate the binding of the product, cellobiose, and several inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(78 citation statements)
references
References 52 publications
6
72
0
Order By: Relevance
“…The overall fold is homologous to other GH7 cellobiohydrolases, comprising a globular and equatorially elongated protein, but with several interesting features particularly in the surface loop regions (Fig. 2B) (33,(38)(39)(40)(41). The active site tunnel, formed by four pairs of curved antiparallel β-sheets packed face to face, extends from the −7 binding site at Trp57 to the +2 binding site near Phe362, representing a distance of ∼48 Å between the tunnel entrance and exit.…”
Section: Resultsmentioning
confidence: 99%
“…The overall fold is homologous to other GH7 cellobiohydrolases, comprising a globular and equatorially elongated protein, but with several interesting features particularly in the surface loop regions (Fig. 2B) (33,(38)(39)(40)(41). The active site tunnel, formed by four pairs of curved antiparallel β-sheets packed face to face, extends from the −7 binding site at Trp57 to the +2 binding site near Phe362, representing a distance of ∼48 Å between the tunnel entrance and exit.…”
Section: Resultsmentioning
confidence: 99%
“…All eight glucosyl residues are in the chair conformation, and an intact chain would likely feature a glucosyl residue in subsite -3 also exhibiting a chair conformation. The product binding sites (+1/+2) are occupied in the so-called 'Slide' mode in this structure [63]. This conformation is not active for hydrolysis, as the distance from the -1 anomeric carbon to the nucleophile is 7.1 Å.…”
Section: Mechanisms Of Processivity In Gh Family 7 Cbhsmentioning
confidence: 99%
“…This catalytically-active complex may resemble the theoretical model of the Michaelis complex of T. reesei Cel7A (PDB code 8CEL, Figure 2, bottom right). Immediately following the first catalytic step (Glycosylation), the cellobiose product resides in what we refer to as the 'Unprimed glycosyl-enzyme intermediate' (GEI) mode (seen in PDB structures 6CEL, 7CEL, 1Q2E, 1Z3W, 2RFY, 4HAP, 4IPM, and exemplified by the 7CEL structure in Figure 2, lower left frame) [21,44,63,69,70]. As with the Michaelis complex, no GEI crystal structure has been published to date for a GH Family 7 member.…”
Section: Mechanisms Of Processivity In Gh Family 7 Cbhsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystallization in the presence of foreign materials has also been studied using the seeding technique to obtain crystals [18][19][20]. Representative structural analysis for binding between endoglucanase (AaCel9A) [19] and cellobiose or cellobiohydrolase (Pc_Cel7D) [20] and cellobiose showed that for Aa-Cel9A and Pc_Cel7D, cellobiose binds in three glucosyl-binding subsites (−1, −2, and +1) and two glucosyl-binding subsites (+1 and +2), respectively. Binding sites in Pc_Cel7D are close to the exit of the cellulose-binding cleft.…”
Section: Introductionmentioning
confidence: 99%